1995
DOI: 10.1016/1074-5521(95)90089-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular recognition in the bovine immunodeficiency virus Tat peptide-TAR RNA complex

Abstract: We have identified a new structural motif for protein-RNA recognition, a beta-hairpin peptide that interacts with the RNA major groove. Specificity is associated with formation of a novel RNA structural motif, a U.AU base triple, which facilitates hydrogen bonding of an arginine residue to a guanine and to a backbone phosphate. These results should facilitate the design of inhibitors that can disrupt HIV Tat-TAR association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
229
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 186 publications
(240 citation statements)
references
References 23 publications
9
229
2
Order By: Relevance
“…In agreement with this observation, Varani and co-workers [14] showed that free TAR contains a large degree of helical discontinuity, leading to a more accessible major groove that forms the contact area with the peptide. The structure of the BIV TAR Tat peptide complex shows that the peptide containing the basic sequence region of the BIV Tat protein adopts a I~-turn conformation and also binds to the widened major groove of the BIV TAR RNA [15,16]. The experimental results on Tat-TAR interactions for BIV and HIV-1 thus seem to become more consistent, and a fuller picture emerges.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In agreement with this observation, Varani and co-workers [14] showed that free TAR contains a large degree of helical discontinuity, leading to a more accessible major groove that forms the contact area with the peptide. The structure of the BIV TAR Tat peptide complex shows that the peptide containing the basic sequence region of the BIV Tat protein adopts a I~-turn conformation and also binds to the widened major groove of the BIV TAR RNA [15,16]. The experimental results on Tat-TAR interactions for BIV and HIV-1 thus seem to become more consistent, and a fuller picture emerges.…”
Section: Discussionmentioning
confidence: 91%
“…As the TAR spectrum was only marginally distorted on TAR binding to Tat, the difference-CD spectrum derived from the TAR-BP1 complex and free TAR (Fig. 5) should provide a rough guess of the CD spectrum of the bound peptide, and previous studies show that difference-CD spectra are well suited to predict the secondary structures correctly [15,16,29]. According to this procedure, the minimum of molar ellipticity is shifted to 217 nm, an effect typical of polypeptides adopting extended conformations, such as 13-strands [28].…”
Section: Spectroscopymentioning
confidence: 92%
See 1 more Smart Citation
“…1A) (17-19). On binding to the TAR site, the Tat peptide adopts a ␤-hairpin conformation nestled deep within the major groove of the TAR RNA (20,21). Using structural information as a guide, a permuted BIV-1 TAR site was placed near the 5Ј-end of every molecule within an RNA pool.…”
Section: Resultsmentioning
confidence: 99%
“…These general recognition principles could also be common to proteins that contain other motifs enriched in arginine and glycines. For example, the NMR structures of a complex between a bovine immunodeficiency virus (BIV) transactivation response element (TAR) and a peptide from a transactivating protein (Tat) showed that the peptide adopts a β-turn conformation and sits in the major grove of the RNA, where it forms base-specific contacts with RNA using glycines and arginines (54,55).…”
Section: Discussionmentioning
confidence: 99%